Open Legal Policy: Testing Practices and Limitations by the Constitutional Court - Riqiey, Baharuddin; Hadi, Syofyan; Sukardi, Sukardi; Hikam, Reza Maulana (Jurnal Hukum Magnum Opus, 2025)
The Constitutional Court in its various decisions has not granted a petition on the grounds of open legal policy. Open legal policy is always identical to numbers, for example, term of office, parliamentary threshold, etc. Therefore, the purpose of this study is to examine and analyze the practice of testing legal norms that are open legal policy by the Constitutional Court and to examine and analyze the limitations of testing legal norms that are open legal policy by the Constitutional Court. The research method used in this study is legal research with a statutory, conceptual, and case approach. The results of this study indicate that the practice of testing legal norms that are open legal policy has been going on since the Constitutional Court was established. The provisions of legal norms that are open legal policy are essentially the absolute domain of the legislators so that other state institutions cannot change these provisions. However, under certain conditions the Constitutional Court can change these provisions as long as the norms clearly violate morality, rationality, and intolerable injustice; exceed the authority of the legislators; are part of the abuse of authority; cause institutional problems and lead to legal deadlock; are contrary to political rights; and are contrary to the principle of people's sovereignty.